Effect of electrospun nisin and curcumin loaded nanomats on the microbial quality, hardness and sensory characteristics of rainbow trout fillet - Meral, Raciye; Alav, Aslihan; Karakas, CananYagmur; Dertli, Enes; Yilmaz, Mustafa Tahsin; Ceylan, Zafer (ELSEVIER, 2019)
Nisin and curcumin loaded (NCL) nanomats having 172 nm mean diameter were successfully fabricated. The effect of NCL nanomats in terms of limitation of Total Mesophilic Aerobic (TMAB) and Lactic acid bacteria (LAB) in fish fillets was tested during the analysis period. On the 4th day, while TMAB load of C was 6.61 log CFU g(-1), that of the sample coated with NCL nanomats was found to be 3.28 log CFU g(-1). TMAB load of control samples reached above 6 log CFU g(-1) on the 4th day of cold storage, TMAB load of fish samples coated with nanomats reached the same level up to the 12th day. The shelf life of coated fillets was extended to 12 day. 3-4 logarithmic decrease was obtained in LAB count by NCL nanomats during the analysis period. On the 4th storage day, the hardness value of C sample decreased 21% compared to NCL samples. All sensory attributes of C samples were acceptable by the 4th day of the storage; while sensory attributes of NCL samples were acceptable by the 10th day of storage. The study revealed that nisin and curcumin loaded nanomats could be effectively used to improve the quality of fish fillets.
Keywords: Bacteriocin; Curcumin; Electrospinning; Nisin; Nanomats; ESSENTIAL OIL; ONCORHYNCHUS-MYKISS; LACTIC-ACID; FISH; NANOFIBERS; MONOCYTOGENES; STABILITY; CINNAMON; BACTERIA; TEXTURE; Food Science & Technology